Priorities of energy saving and energy efficiency aimed at reducing the energy intensity of the GDP of the Republic of Kazakhstan - Karenov , R.S. (BUKETOV BUSINESS REVIEW, 2017)
It is proved that there are now many sectors of Kazakhstan's economy, including industry, the construction sector and housing and communal services, in terms of energy consumption is largely ineffective. It is emphasized that the government is doing a great work aimed at overcoming these problems. It is noted that it is impossible to achieve a successful energy efficiency without the use of a standard set of technologies and tools that can be grouped on the basis of the impact. The conclusion is that the attraction of strategic investors in the sphere of energy saving through an international cooperation mechanism - a problem arising from the 100 steps, designated by the President of Kazakhstan, development of domestic market of energy services. The attention is focused on the fact that the modernization of housing and communal services carried out in the framework of the program "Nurly Zhol", it remains an important aspect of public policy upon which the housing and communal sphere becomes one of the drivers of economic growth. It is noted that during the years of industrialization, huge work was carried out at the same time to develop the infrastructure. A reliable energy system has been created. A regulatory and legal framework was established in the sphere of energy saving. The expected result of the country until 2020 will be a reduction in the energy intensity of the gross domestic product of the Republic of Kazakhstan through the effective using of energy resources. The policy of energy and resource saving will allow the transition to "green" development and increase the competitiveness of the national economy.